Небо на двоих: [роман] / Ирина Мельникова - Мельникова Ирина Александровна (Незнакомка, 2011)
Экземпляры: ф. 4 (20120216) / Инвентарный номер: 98007 / Цена: 94.00 / Авт.знак: М 48 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6